Tinjauan Yuridis Terhadap Pelaku Usaha Penjualan Kosmetik Ilegal Di Indonesia (Putusan Nomor : 1743/Pid.Sus/2021/Pn Mdn) - Hot Prinauli Purba, Iin; Ompusunggu, Milka; Walace Manullang, William; Mark Manullang, Michael (Universitas Ekasakti, 2023)
Cosmetics have become one of the business fields that provide hope for business actors, from cosmetics that have a distribution permit from the government to cosmetic products that are ilegal or do not have a distribution permit. This is due to weak supervision in the field of standardizing the quality of goods and regulatory products, which has the impact that many cosmetic products distributed on the market are not registered standards and do not meet quality standards and also have distribution permits from the Food and Monitoring Agency (BPOM). This type of research is carried out using normative juridical legal research methods or is often called document study or library research. This research provides useful input and adds knowledge and insight into the world of cosmetics, especially regarding matters related to the criminal act of selling cosmetics and ilegal pharmaceutical preparations. Apart from that, it is also a material for deeper study in order to create scientific concepts that can provide input in the development of law enforcement against ilegal cosmetics sales businesses in Indonesia.